Предмет: Алгебра,
автор: Аноним
решите уравнение
(х+9)(3-х)=0
заранее спасибо
Ответы
Автор ответа:
0
(x+9)(3-x)=0
3x-x2+27-9x=0
x2+6x-27=0
D=36+27*4=144
корень из D=12
X1=(-6+12)/2=3
X2=(-6-12)/2=-9
Автор ответа:
0
(х+9)(3-х)=0
Произведение равно нулю, когда хотя бы один из множителей равен нулю, значит
х+9=0 или 3-х=0
х=-9 -х=-3
х=3
Ответ:х=-9, х=3
Похожие вопросы
Предмет: Литература,
автор: frankhalk
Предмет: Литература,
автор: frankhalk
Предмет: Информатика,
автор: baditka
Предмет: Химия,
автор: Denis2322